Archival Analysis of Service Desk Research: New Perspectives on Design and Delivery - Rahman, Md Istehadur; Eden, Rebekah; Alarifi, Abdulrahman Hamad E; Sedera, Darshana (ACIS, 2014)
Our analysis of service desk studies shows the extent to which researchers have neglected important aspects of service desk design and delivery. The observations are made through an archival analysis of 58 peer reviewed publications in top tier outlets. Our analysis led to the development of a generic framework which identified three themes in service desk design – (1) user groups, (2) support models, and (3) technology types – and two themes in service desk delivery – (1) direction of delivery, and (2) executive support level. This paper makes a twofold contribution to service desk research. First, it provides an understanding of service desk functions and the challenges faced by organisations in delivering those functions. Second, it identifies established and emerging areas in the service desk field. This archival analysis is the first attempt to systematically analyse the service desk literature.